An event study of institutions and currency crises - Pattama L. Shimpalee (2018)
We use event study methodology to examine the behavior of seven institutional variables eighteen months prior to and after a currency crisis. Our data on institutions include bureaucratic quality, corruption, ethnic tensions, external conflict, internal conflict, government stability, and law and order over the period 1984-2002. Our country coverage includes forty industrial, emerging market, and developing economies for various regions of the world. The graphical event study shows that there are many instances where institutions are weaker in periods before and after a currency crisis than during tranquil periods. The evidence is most compelling for government stability, law and order, bureaucratic quality, and corruption. We also test for differences in the mean values of institutional variables in turbulent periods around a crisis event and tranquil, non-crisis periods. Results from our tests generally complement evidence from the event study. © 2006 Elsevier Inc. All rights reserved.